PENYULUHAN PUTRI SETIA (SEHAT TANPA ANEMIA) DAN PEMBAGIAN TABLET FE - Andi Yulia Kasma; Sitti Nurhadijah; Andi Ayumar; A. Asyratul Hidayah (Jurnal Pengabdian Masyarakat Gerakan Aksi Sehat (GESIT), 2024)
Young women are required to take FE tablets because they experience menstruation every month. FE tablets are also useful for replacing iron lost due to menstruation and for meeting iron needs that are not sufficient from food. In general, the symptoms of anemia that are often felt are lethargy, weakness, fatigue, negligence, frequent complaints of dizziness and dizzy eyes. Further symptoms are pale eyelids, lips, tongue, skin and palms. Treatment of anemia can be done independently by taking oral iron therapy or Fe tablets appropriately. This community service method is a counseling method in the form of lecture material and direct presentation related to loyal daughters (healthy without anemia) and direct distribution of Fe tablets. 20 female students. as a whole it was very effective, resulting in an increase in the knowledge of young women in adherence to taking iron tablets. Furthermore, it is hoped that from this activity young female students at SMP Negeri 2 Bangkala Barat can routinely consume blood-boosting tablets to prevent anemia. Keywords: blood supplement tablets, teenage girl, anemia